(untitled) (Marketing Journal, 2025)
This study is devoted to the analysis of the territorial development criteria and development models of cotton -textile clusters. Clusters play a strategic role in integrating the agricultural and industrial sectors to enhance production efficiency, expand export potential, and ensure regional employment. The research findings indicate that the harmonization of regional -economic potential, technological integration, and governance mechanisms is a critical factor for sustainable 385 development. Furthermore, models such as comprehensive resource utilization, innovation -integration, regional diversification, and digital management significantly contribute to increasing cluster efficiency and expanding export capacity.